Unmanned Free Balloon Flight’s Integration into Unmanned Aircraft System Traffic Management - Hegyi, Norbert; Jósvai, János (Acta Technica Jaurinensis, 2019)
This paper describes and inspects unmanned aerial vehicle, unmanned aircraft system, unmanned aircraft system traffic management, light and medium unmanned free balloons. It presents future safety developments and goals of the European Union’s own airspace, but also the Hungarian free route airspace. The development and realization of Swiss U-Space is discussed. Hungarian flights statistics are analyzed. Based on statistics, realized and under development solutions there are recommendations in the paper for the integration of the flight tacking for the mentioned balloons. A real flight tracking test has been done and it is shown in this paper. Its properties are analyzed with conclusions for possible usage.